Influence of Compensation, Work Environment, and Job Promotion on Organizational Commitment of Employees of PT. United Tractors Malinau North Kalimantan - Kristira, Asri -; Prayekti, Prayekti -; Kirana, Kusuma Chandra (Admisi dan Bisnis, 2024)
This research was conducted with the aim of finding out the influence of compensation, work environment, job promotions on the organizational commitment employees of PT. United Tractors Malinau, North Kalimantan. This research uses quantitative methods, and the population is all employees of PT. United Tractors Malinau, North Kalimantan, totaling 50 employees using total sampling techniques. The data collection method was carried out by observing and distributing questionnaires. The research results show that compensation has a significant effect on organizational commitment, the work environment does not have a significant effect on organizational commitment, and job promotions have a significant effect on organizational commitment. Simultaneously, compensation, work environment and job promotions have a significant effect on organizational commitment.